2008
DOI: 10.1016/j.childyouth.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Examining African American fathers' involvement in permanency planning: An effort to reduce racial disproportionality in the child welfare system

Abstract: Examining African American fathers' involvement in permanency planning: An effort to reduce racial disproportionality in the child welfare system. Children and Youth Services Review, 30, 407-417.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…This finding is consistent with those of other studies that describe fathers' waning participation during permanency planning activities and involvement interventions (see Coakley, 2008 andO'Donnell, 1999). The reasons why fathers initially participate and then later quit must be understood and addressed to improve fathers' retention during their children's stay in foster care.…”
Section: Engaging and Retaining Fathers In Case Planningsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistent with those of other studies that describe fathers' waning participation during permanency planning activities and involvement interventions (see Coakley, 2008 andO'Donnell, 1999). The reasons why fathers initially participate and then later quit must be understood and addressed to improve fathers' retention during their children's stay in foster care.…”
Section: Engaging and Retaining Fathers In Case Planningsupporting
confidence: 81%
“…Such involvement included providing financial support and participating in visitation. Coakley (2008) presented findings obtained from a secondary analysis of foster care placement data of 88 African American and Hispanic/Latino children for whom she investigated length of stay and case plan compliance by the children's fathers. The analysis identified 60 biological fathers and males who assumed the father role.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fathers experience a number of barriers to their child welfare involvement, which adversely affects their children's permanency outcomes (Coakley, 2008(Coakley, , 2012Malm et al, 2008). Some barriers are attributed to their own personal problems, such as substance abuse and mental illness (Jaffee, Caspit, Moffitt, Taylor, & Dickson, 2001;Waller & Swisher, 2006), and familial problems, such as, co-parenting and domestic violence issues (Allen & Hawkins, 1999;McLanahan, & Beck, 2010).…”
Section: Barriers To Involvementmentioning
confidence: 98%
“…To date, most studies are limited to surveying case workers for their opinions about fathers (see Malm, Murray, & Geen, 2006;O'Donnell, 1999;O'Donnell, Johnson, D'Aunno, & Thornton, 2005) or examining agency case records with fractured father data (see Brown, Callahan, Strega, Walmsley, & Dominelli, 2009;Coakley, 2008Coakley, , 2012 in an attempt to piece together an accurate picture of father involvement. Unquestionably, the use of these methods has provided invaluable descriptive and corollary data on father involvement from an agency perspective, which has resulted in prescriptive steps to identifying, locating, and engaging fathers.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, it has been suggested that the lack of empirical knowledge on fathers' involvement in the child welfare system limits our ability to discern prohibitive and/or promotive factors of father involvement, which could ultimately influence child welfare outcomes (Coakley, 2008). In the current study, the Responsible Fathering framework served as an organizational structure in the examination of factors that may inhibit responsible fathering.…”
Section: Introductionmentioning
confidence: 99%